Research Protective Metal Coatings to Face the Elements - Makhammadjanov Khusanboy Alisher o‘g‘li; Otaqo‘ziyev Akramjon Adakhamjonovich; Mutalipov Xojiabdullo O‘ktamjon o‘g‘li (Research Parks Publishing LLC, 2021)
This article describes the methods of coating polymer coatings and the work efficiency of the coating coated details. Polymeric coatings are made of polymeric materials and can be applied on a number of substrates using a variety of methods such as extrusion/dispersion and solution casting techniques. Polymeric coatings provide excellent adherence to and protection from the environment